Self-pathologizing, self-condemning, self-liberating: Youths' accounts of their ADHD-related behavior. (February 2016) - Honkasilta, Juho; Vehmas, Simo; Vehkakoski, Tanja
Abstract: This study analyzes the discursive construction of attention deficit hyperactivity disorder (ADHD) and self in relation to a socioculturally shared understanding of moral norms. Thirteen Finnish youth aged 11 to 16 diagnosed with ADHD were interviewed during this discourse analysis study. The youth accounted for their culturally undesirable behavior, performance and traits through three different types of accounts: (1) externalizing personal responsibility due to a compelling medical condition, (2) internalizing personal responsibility through moral self-condemnation, and (3) distancing oneself from the socially imposed stereotypes and stigmas related to ADHD. This study challenges dominant understanding of young people with a diagnosis of ADHD and contributes to our understanding of how ADHD is constructed in their lives. Highlights: Discourse analysis of accounts of youth of their ADHD-related behavior and traits. Youth actively engage with the ADHD label and weigh its meaning in their lives. ADHD is given varying meanings with different effects on constructing moral selves. In interaction, ADHD both exempts from moral responsibility and poses social stigma. This study challenges the dominant understanding of youth with a diagnosis of ADHD.